Biopreparations: Types, main agents, and promising methods - Sultanova Lola; Pronovich Nataliya; Galieva Gulnaz; Kuryntseva Polina; Selivanovskaya Svetlana (BIO Web of Conferences)
The article analyses the market of biopreparations used in agriculture in Russia and globally. A comparative analysis of data on biopreparations registered in the State Catalogue of Pesticides and Agrochemicals Authorised for Use in the Russian Federation and the European Union Pesticides Database - (EU Pesticides Database - Active substances) was carried out. On the basis of this analysis, microorganisms used in the production of biopreparations in Russia and European Union countries were selected. The differences between the number of registered microorganisms in these states were identified, and the characteristics of the most widely used microorganisms as components of biopreparations were described.